The effectiveness of SSC English syllabus in motivating students to achieve communicative competence: A case study - Sima, Tahmina Sultana (IIUC Studies, 2020)
This study aims at examining the effectiveness of present Secondary School Certificate (SSC) English syllabus in order to find out what role this syllabus plays in motivating students to achieve communicative competence. Using a mixed-method approach, I conducted this study by collecting data from eighty seven students of SSC level through a questionnaire, and from five English teachers by interviewing them. This study revealed that most of the students of SSC level are not motivated enough to achieve communicative competence, rather they memorize selected answers provided by their teachers or from their guide-books to secure a good Grade Point Average (GPA) in SSC examination. It further revealed that the present syllabus is effective in making students motivated only to some extent, and that is because of some activities provided in the syllabus. But yet students have not been able to achieve communicative competence as they do not practise these activities properly. Based on these findings, some steps have been recommended to overcome this problem. IIUC Studies Vol.15(0) December 2018: 47-58